PHYSIOTHERAPY MANAGEMENT IN INDIVIDUAL WITH WRIST DROP AFFECTED BY LEPROSY: A CASE REPORT - Endrawati, Mira Yuga; Sari, Dwi Rosella Komala; Prihastomo, Teguh (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Leprosy is a skin disease caused by Mycobacterium leprae, which is an intracytoplasmic parasite on macrophages and Schwann cells. This bacterium attacks the peripheral nerves, especially the Schwann cells. Mycobacterium leprae was first discovered by a Norwegian named Gerhard Armauer Hansen. One of the consequences of peripheral nerve disorders in people with leprosy is drophand/wrist drop/finger drop caused by damage in radial nerve. Case Presentation: A male patient aged 29 years, at the Kelet’s Hospital, Jepara, Central Java, on January 11, 2021 in a bed rest phase, had a fever of 37.8 C. His diagnose was wrist drop affected by leprosy. The condition of the skin was dry and peeled and indicated wrist drop. Previously, the patient had treated at one of the health centers in Juwana city, Central Java, and received the 4th MDT, the haemoglobin was 7 and already received a blood transfusion. Thus, the patient was referred to Kelet’s Hospital to get better treatments and the doctor suggested to do physiotherapy treatment. Management and Outcome: The interventions used the virgin coconut oil (VCO) Oil, passive, active assisted and stretching for 3 sessions. The impairments were limitation movement for wrist flexion and extension. The evaluation carried out the Manual Muscle Testing (MMT) to measure the muscle strength of wrist flexion and extension and the xerosis problem value applied by Overall Dry Skin Score (ODSS). Discussion: After 3 sessions, the physical examination declaired muscle strength for wrist flexion and extension had the same pattern was 3 of 5 and xerosis problem had not decreased yet. The second treatment reported muscle strength was not increasing, however the skin condition was more moist. The third evaluation found a reduction of xerosis condition, as well as increased muscle strength for wrist flexion and extension were 4 of 5. Conclusion: A management of physiotherapy used VCO Oil and exercise therapy applied passive, active assisted and stretching in patients with wrist drop affected by leprosy, reported giving positive effects to xerosis condition and able increase muscle strength of flexion and extension of wrist joint.